A cost analysis comparing seasonal malaria chemoprevention with and without Vitamin A supplementation among under-5 children in Nigeria - Olusola Bukola Oresanya; Olujide Arije; Jesujuwonlo Fadipe; Kunle Rotimi; Abimbola Phillips; Kolawole Maxwell; Emmanuel Shekarau; Nneka Onwu; Eva S. Bazant (PLoS ONE, 2025)
Background Child mortality in Nigeria, significantly affected by malaria and malnutrition, remains a public health concern in the country. Seasonal Malaria Chemoprevention (SMC) and Vitamin A supplementation (VAS) are effective interventions that can be delivered through integrated health campaigns to reduce this mortality. This study assesses the cost implications of integrating these two interventions among under-5 children in Northeast Nigeria. Methods A cost analysis compared standalone SMC (Cycle 1 in July 2021) with SMC-VAS integrated campaign (Cycle 4 in October 2023) in two Local Government Areas (LGAs) in Bauchi State. The number of children reached by the SMC-only campaign was 168,820 and for the SMC + Vit A campaign, the number was 170,681. Data collection utilized a mixed-methods approach, drawing from primary and secondary sources, including programmatic, financial, and coverage records. Costs were categorized into distribution, Sulphadoxine-Pyrimethamine plus Amodaiquine (SPAQ) for SMC, Vitamin A, training, supplies, meetings, labor, supervision, and social mobilization costs. Sensitivity analyses evaluated the effect of a 10% fluctuation in the costs of distribution, labor, SPAQ, and supplies on the cost per child. Results The total cost for the SMC standalone campaign was US$158,934, and the SMC-VAS integration was US$186,426. Distribution and drug costs were the largest contributors in the integrated and SMC-only campaign. The SMC-only cost per child was $0.94 and $1.18 when eligible children received both SMC and VAS. The integration of VAS into the SMC campaign cycle incurred an additional US$27,492 over Cycle 1 cost (US$186,426 – US$158,934). Fluctuations in distribution costs were the most influential component of the cost per child. Conclusion Integrating VAS with SMC campaigns increases the cost by US$0.24 per child, a modest increment considering the potential health benefits. The results support the feasibility of this integration, in terms of cost, to combat child mortality from malaria and malnutrition in Nigeria. Further research is recommended to explore the cost-effectiveness of this integrated distribution model.